AMS data of small scale marble shear zone, Viana do Alentejo, Ossa-Morena Zone, Portugal, complemented with microstructural and chemical data - Vladimír K Kusbach; Zuzana Roxerová; Matěj Machek; M Kučeráková; Stanislav Vratislav; Anna Vávrová; Martin Chadima (PANGAEA, 2025)
We studied in 3D detail magnetic fabric in a shear zone in marble. These major data are supplemented with microstructural and chemical composition data. Measurements of anisotropy of magnetic susceptibility (AMS) were carried on 1947 samples from March 2021 to June 2023. Samples were collected in one location at a disused quarry in Viana do Alentejo, Ossa-Morena Zone, Portugal. The shear zone is visible along the quarry wall for approximately 3 meters, with both its displacement and width varying along its length. The maximum displacement (~100 cm) observed within the shear zone is roughly three times its maximum width (~35 cm). Samples were collected during two consecutive campaigns with a portable drilling machine and portable rock saw, respectively. In total 39 drill cores and 14 slabs cut to span the entire deformation gradient of the studied SZ were collected. Larger oriented samples were subdivided to individual samples in a preparation room and measured on the MFK 1 Kappabridge apparatus in the magnetic lab of the Institute of Geophysics, Academy of Sciences of the Czech Republic. This study gave an opportunity to investigate the relationship between AMS and strain in natural rocks. As AMS reflects the cumulative magnetic signal of the crystallographic and shape-preferred orientations of all mineral grains that constitute the rock volume, it can be used to connect the rock microstructure and withstand deformation. Dataset is published in the specimen coordinate system. Due to the diverse nature and orientation of AMS samples and for simplicity and clarity, all data have been rotated and presented in a common local coordinate system, specifically a perpendicular view of the sampled quarry wall (orientation 222/90 DD/D).